Persuasion - Austen, Jane, 1775-1817 (London : Oxford University Press, H. Milford, 1930)
The author's last complete novel tells the story of young Anne elliot as she moves from the Somerset countryside to Lyme Regis and Bath
Persuasion is the last novel fully completed by Jane Austen. It was published at the end of 1817, six months after her death. The story concerns Anne Elliot, a young Englishwoman of 27 years, whose family is moving to lower their expenses and get out of debt, at the same time as the wars come to an end
Keywords: Elliot, Anne -- (Fictitious character), -- 1787- -- Fiction; Ship captains -- Fiction; Rejection (Psychology) -- Fiction; Young women -- Fiction; Motherless families -- Fiction; England -- Fiction; Fiction; Novels; Romance fiction